Health-care practitioners' assessment and observations of birth trauma in mothers and partners. (2nd January 2022) - Delicate, Amy; Ayers, Susan; McMullen, Sarah
ABSTRACT: Background: Evidence shows that traumatic childbirth can cause ongoing distress, often referred to as birth trauma. This can have an impact on parents and the couple relationship, and consequently identifying and supporting parents with birth trauma is important to practice. Aim: To investigate the experiences of health-care practitioners from the United Kingdom (UK) in assessment for birth trauma, perceived occurrence of birth trauma and observed impact on parents and the couple relationship. Methods: An online survey of UK health-care practitioners working with parents in the first postnatal year. Results: A sample of 202 practitioners reported identifying birth trauma in 34.4% of mothers and 25.0% of partners. Assessment for birth trauma was only conducted for 50.3% of mothers and 25.9% of partners. The most observed symptoms were re-experiencing among mothers (87.1%) and avoidance among partners (50.9%). Birth trauma was perceived as impacting on the couple relationship for 29.8% of mothers and 26.9% of partners. Written responses provided more detailed observations of the impact of birth trauma. Conclusion: Understanding how birth trauma may present differently in mothers and partners could support effective assessment. Once birth trauma is identified, parents require personalised support to help them cope with the impact.